The longitudinal effect of parental support during adolescence on the trajectory of sport participation from adolescence through young adulthood - Chung Gun Lee; Seiyeong Park; Seunghyun Yoo (Journal of Sport and Health Science, 2018)
Background: One efficient way to increase physical activity is through sport participation because participation in sport activities inherently includes many enjoyable aspects, such as social interaction, competition, personal challenge, and goal achievement. The main purpose of this study was to investigate the longitudinal effect of parental support during adolescence on the trajectory of sport participation from adolescence through young adulthood. Methods: The data used in this study came from the National Longitudinal Study of Adolescent to Adult Health (Add Health). It is a 4-wave longitudinal study that followed up a nationally representative sample of middle and high school students in the US. A series of multilevel logistic regression models were used to examine the effect of parental support at Wave 1 on the trajectory of sport participation from Wave 1 to Wave 4. Results: The effect of parental support during adolescence on participants' sport participation lasted until they become young adults (Wave 3) (p < 0.001). Among the male participants, parental support at Wave 1 was a significant predictor for sport participation at Waves 1, 2, and 3 (p < 0.001). However, a significant effect of parental support at Wave 1 on sport participation in early young adulthood (Wave 3) becomes insignificant when adjusting for self-esteem and depression. Among the female participants, parental support at Wave 1 was a significant predictor for sport participation at Waves 1, 2, and 3 (p < 0.01) even after depression and self-esteem were introduced into the model. That is to say, unlike male participants, parental support during adolescence has an independent effect on sport participation from adolescence (Wave 1) through early young adulthood (Wave 3) over and above the effects of depression and self-esteem in female participants. Conclusion: The results of this study contributed to the literature by providing important information on the longitudinal effect of parental support during adolescence on the trajectory of sport participation from adolescence through young adulthood using a nationally representative sample of participants transitioning from adolescence to young adulthood.